PLATELET VOLUME INDICES (PVI) IN METABOLIC SYNDROME (MS) - DR. DHARMIK S. PATEL; DR. KILLOL N. DESAI; DR. BHAKTI N. GAMI; DR. HETAL J. JOSHI; DR. JYOTI P. SAPRE (International Journal of Pharma and Bio Sciences, 2014)
The metabolic syndrome (MS) is characterized as the clustering of closely associated and interdependent atherosclerotic risk factors.The study was performed to analyse platelet volume indices (PVI) that are useful for identifying large platelets, which are haemostatically more active and produce more thromboxane A2. We measured PVI in 44 subjects with metabolic syndrome (age 51±10 years) and 43 subjects without metabolic syndrome (age 49±15 years). The PVI was significantly higher in patients with metabolic syndrome compared to control group (p <0.0001). PVI is simple, effortless and cost effective tool for predicting the possibility of impending acute events. So, PVI may be used as a better predictor for acute complication in patients with metabolic syndrome.